The Effect of Organizational Culture on Entrepreneurship Characteristics and Competitive Advantage of Small And Medium Catering Enterprises in Makassar - Abdullah, Salma; Musa, Chalid Imran; Azis, Muhammad (International Review of Management and Marketing, 2017)
This research aimed to examine, analyze, and explain empirically the effect of organizational culture on entrepreneurship characteristics and competitive advantage of small and medium catering enterprises in Makassar. This research is an explanatory research that tested the hypothesis by investigating the effect of organizational culture on entrepreneurship characteristics and competitive advantage of small and medium catering enterprises in Makassar. This research used survey method with cross-sectional data collection through questionnaires. The samples were selected using simple random sampling with the size of 200 employees. Data analysis method used in testing the hypothesis of this research was Structural Equation Modeling (SEM). The findings of this research reveal that organizational culture has a positive and significant effect on entrepreneurship characteristics and organizational culture has a positive and significant effect on competitive advantage of small and medium catering enterprises in Makassar. Keywords: Organizational culture, entrepreneurship characteristics, competitive advantage JEL Classifications: L2, L26